1997
DOI: 10.1088/0031-9155/42/5/005
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet and visible spectroscopies for tissue diagnostics: fluorescence spectroscopy and elastic-scattering spectroscopy

Abstract: We review the application of fluorescence spectroscopy and elastic-scattering spectroscopy, over the ultraviolet-to-visible wavelength range, to minimally invasive medical diagnostics. The promises and hopes, as well as the difficulties, of these developing techniques are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
196
0
19

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(215 citation statements)
references
References 78 publications
0
196
0
19
Order By: Relevance
“…Many types of probes have been used within the research community and cannot all be summarized here; however, comprehensive reviews of DRS, LIFS, and RS probe technology are available. 34 Briefly, combination LIFS-DRS probes have been demonstrated by past studies, 35,36 as well as a probe combining all three techniques. 32 There are several important, and challenging, design and functional considerations for a probe that combines reflectance, fluorescence, and Raman signals.…”
Section: Fiber-optic Probesmentioning
confidence: 98%
“…Many types of probes have been used within the research community and cannot all be summarized here; however, comprehensive reviews of DRS, LIFS, and RS probe technology are available. 34 Briefly, combination LIFS-DRS probes have been demonstrated by past studies, 35,36 as well as a probe combining all three techniques. 32 There are several important, and challenging, design and functional considerations for a probe that combines reflectance, fluorescence, and Raman signals.…”
Section: Fiber-optic Probesmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] This technology is cost-effective, and can be deployed through fiber optic probes to quickly, nondestructively, and quantitatively detect the structural, physiological, and biochemical changes that are associated with the progression of disease. Several studies have demonstrated that there are significant differences in the fluorescence [1][2][3]5,7,9,11 and diffuse reflectance 4,13-17 spectra of normal, benign, and malignant breast tissues, which could be used for the diagnosis of breast malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Elastic scattering spectroscopy (ESS) is an emerging technique for generating a wavelength spectrum that reflects structural and morphological changes within tissues (Bigio and Mourant 1997;Green et al 2014). ESS has been shown to be sensitive to nuclear size, chromatin content, and nuclear/cytoplasmic ratio-all of which characteristics are of interest to the histopathologist who is screening for malignancy within tissue (Wallace and Van Dam 2000).…”
Section: Elastic Scattering Spectroscopymentioning
confidence: 99%